Kesiapan Produsen Mebel di Jepara dalam Menghadapi Sertifikasi Ekolabel - Herry Purnomo; Rika Harini Irawati; Ririn Wulandari (Jurnal Manajemen Hutan Tropika, 2011)
Furniture is a big 4 of Indonesia’s export commodities with palm oil, textiles, and rubber outside the oil and gas. Value-added is enjoyed by tens of millions of people involved in the value chain. But, the business is experiencing severe challenges to the issue of certification and forest products (green or certified furniture) and the scarcity of wood. Certified furniture is intended for preservation of forest resources, the healthy processing of furniture making as well as improving the welfare of artisans. From the supply side of certified furniture, large producers have been prepared while small producers are not ready. From the demand side, domestic consumers only want to pay less for certified furniture, while British and Norway consumers are 16% 7.5% respectively. The increase in willingness to pay is lower than the certified furniture prices increased between 6–30%., Certification can be done by a third party accredited by the Tropical Forest Trust (TFT), Indonesian Ecolabel Institute (LEI), or Forest Stewardship Council (FSC). When the increase in production costs are higher than the desire of consumers to pay, then the certified furniture becomes difficult to be realized. Need specific strategies to market certified furniture. This article is a case study in Jepara furniture craftsmen who accounted for 10% of national exports.